State policies toward indigenous peoples in Latin America : issues and alternatives - Van Cott, Donna Lee (Inter-American Dialogue WashingtonUS, 1994)
Describes the development of indigenous movements in Latin America at the national and international levels. Details policy issues that cause conflict between indigenous peoples and nation-states. Makes recommendations.